The Kinetics Reaction of Phosphoric Acid Formation from Cow Bone - Pujiastuti, Caecilia; Yustina Ngatilah; Muhammad Septianto; Angelia Tantyono (Journal of Research and Technology, 2020)
Phosphoric acid can be formed from bone waste, including cow bone which contains calcium phosphate. When reacted with sulfuric acid it becomes phosphoric acid. The purpose of this research was to determine the reaction constant of phosphoric acid from cow bones. The reaction constant can determine the good operating conditions in a reactor design. Starting with the cow bones that have been powdered with a size of 200 mesh, dissolved in the water until saturated. Then saturated solution 500 ml was taken and reacted with 4 N sulfuric acid 100 ml, stirring process was carried out at 200 rpm, with variable temperature were (70oC, 80oC, 90oC, 100oC, and 110oC) and time were (40, 50, 60, 70, and 80 minutes). Next, the sample was filtered, and the sediment was taken, and analysed of phosphoric acid filter and separated the sediment. Based on this research, an equation k = 1.1627 e -3742.4 / T was generated. The graph in picture 5 shows that the equation followed a pseudo first order reaction.